Epidemiology of Enterocytozoon bieneusi infection in humans - Matos, O. (2012)
A review was conducted to examine published works that focus on the complex epidemiology of Enterocytozoon bieneusi infection in humans. Studies on the prevalence of these emerging microsporidian pathogens in humans, in developed and developing countries, the different clinical spectra of E. bieneusi intestinal infection in children, in different settings, and the risk factors associated with E. bieneusi infection have been reviewed. This paper also analyses the impact of the recent application of PCR-based molecular methods for species-specific identification and genotype differentiation has had in increasing the knowledge of the molecular epidemiology of E. bieneusi in humans. The advances in the epidemiology of E. bieneusi, in the last two decades, emphasize the importance of epidemiological control and prevention of E. bieneusi infections, from both the veterinary and human medical perspectives.